Bridge from Theory to Practice: A Conceptual Framework Fostering Sustainable Business Performance through Green Technology Innovation, Organizational Agility and Employer Branding - Hussain, Altaf; Abdul Wahab, Sazali; Abdul Latiff, Ahmad Shaharudin (Journal of Entrepreneurship, Business and Economics, 2023)
In order to address the harming issues of biodiversity and social isolation, organizations are under pressure to study innovative and sustainable business performance practices. The resource-based view (RBV) and the stakeholder model established a set of values that businesses might use to create a sustainable future. The primary objective of this research was to explore how RBV and the stakeholder theory model support sustainable business performance through organizational agility, employer branding, and green technology innovation. A conceptual framework was built by reviewing the prior literature in order to accomplish the study's goal. This conceptual approach consists of three phases: agility-brand talent attraction measure (ABTAM), innovation, and sustainability. For the purpose to achieve sustainable business performance, organizational agility, employer branding and green technology innovation were supported by previous literature. Although this idea outlines basic concepts. However, it is important to take into account any relevant data in order to bring these steps into integration with the different situations. In order to achieve many aspects of organizational sustainability, this article offers a systematic review of the Resource Based View (RBV) and stakeholder model. Within the context of the RBV and stakeholder model, a conceptual framework was established to create a sustainable business performance. This was accomplished by incorporating organizational agility and employer branding into the context of the model. In this work, both theoretical and practical ramifications are taken into consideration and explained Research paper Keywords: Organizational agility; Employer branding; Innovation; Sustainability; RBV; Stakeholder Reference to this paper should be made as follows: Hussain, A., Abdul Wahab, S., & Shaharudin, A. (2023). Bridge from Theory to Practice: A Conceptual Framework Fostering Sustainable Business Performance through Green Technology Innovation, Organizational Agility and Employer Branding. Journal of Entrepreneurship, Business and Economics , 11 (2), 29–52.